The long history of a melanoma associated with a congenital large plaque type blue nevus with subcutaneous cellular nodules - Francesco Savoia (Mattioli1885, 2015)
The term large plaque type blue nevus with subcutaneous cellular nodules (LPTBN-SN) refers to a huge blue nevus, usually located on the trunk, that develops subcutaneous nodules many years after the lesion has appeared. The potential malignancy of an LPTBN-SN was only discovered in 2012.